Modelling the central bank repo rate in a dynamic general equilibrium framework - Leão, E. R.; Leão, P. R. (Economic Modelling, 2007)
This paper incorporates two components of a modern monetary system into a standard real business cycle model: a central bank which lends reserves to commercial banks and charges a repo interest rate; and banks which make loans under a fractional reserve system and thereby create money. We examine the response of our model to shocks in the monetary base, in the currency-deposits ratio and in the required reserve ratio. Our main finding is that all these monetary shocks lead to changes in the composition of total investment between the banking and the non-banking sectors.